Donor‐targeted serotherapy as a rescue therapy for steroid‐resistant acute GVHD after HLA‐mismatched kidney transplantation. Issue 8 (10th March 2020) - Zuber, Julien; Boyer, Olivia; Neven, Bénédicte; Jollet, Isabelle; Renac, Virginie; Berthaud, Romain; Levy, Romain; Lamarthée, Baptiste; Visentin, Jonathan; Marchal, Armance; Gouge‐Biebuyck, Nathalie; Godron‐Dubrasquet, Astrid; et al.
Abstract : Acute graft‐versus‐host disease (GVHD) is a rare but frequently lethal complication after solid organ transplantation. GVHD occurs in unduly immunocompromised hosts but requires the escalation of immunosuppression, which does not discriminate between host and donor cells. In contrast, donor‐targeted therapy would ideally mitigate graft‐versus‐host reactivity while sparing recipient immune functions. We report two children with end‐stage renal disease and severe primary immune deficiency (Schimke syndrome) who developed severe steroid‐resistant acute GVHD along with full and sustained donor T cell chimerism after isolated kidney transplantation. Facing a therapeutic dead end, we used a novel strategy based on the adoptive transfer of anti‐HLA donor‐specific antibodies (DSAs) through the transfusion of highly selected plasma. After approval by the appropriate regulatory authority, an urgent nationwide search was launched among more than 3800 registered blood donors with known anti‐HLA sensitization. Adoptively transferred DSAs bound to and selectively depleted circulating donor T cells. The administration of DSA‐rich plasma was well tolerated and notably did not induce antibody‐mediated rejection of the renal allografts. Acute GVHD symptoms promptly resolved in one child. This report provides a proof of concept for a highly targeted novel therapeutic approach for solid organ transplantation–associated GVHD. Abstract : This report presents donor‐targeted serotherapy, a therapy based on the adoptive transfer of HLA donor‐specific alloantibodies for the treatment of refractory GVHD occurring after HLA‐mismatched kidney transplantation.